2018
DOI: 10.1080/10810730.2017.1421730
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and Social Media: A Comparison of Traffic about Breast Cancer, Prostate Cancer, and Other Reproductive Cancers on Twitter and Instagram

Abstract: Social media are often heralded as offering cancer campaigns new opportunities to reach the public. However, these campaigns may not be equally successful, depending on the nature of the campaign itself, the type of cancer being addressed, and the social media platform being examined. This study is the first to compare social media activity on Twitter and Instagram across three time periods: #WorldCancerDay in February, the annual month-long campaigns of National Breast Cancer Awareness Month (NBCAM) in Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 41 publications
6
79
1
5
Order By: Relevance
“…However, as described in previous work, [27] we also found that most cancer-related social media posts focus on cancers that predominantly affect women, suggesting that social media does not offer the same appeal as a venue for men's illness narratives. Conceptualized as a space for social support, this observation follows the general trend that men lack the robust social networks often found among women, both virtually and in real life.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…However, as described in previous work, [27] we also found that most cancer-related social media posts focus on cancers that predominantly affect women, suggesting that social media does not offer the same appeal as a venue for men's illness narratives. Conceptualized as a space for social support, this observation follows the general trend that men lack the robust social networks often found among women, both virtually and in real life.…”
Section: Discussionsupporting
confidence: 59%
“…To put our findings in the context of literature on social media and cancer to date, aligned with previous studies, our analysis of posts from National Cancer Survivors Day demonstrates how cancer awareness months promote awareness by the sharing of illness narratives and treatment trajectories on social media. [20,26,27,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social media analytics may also reveal which health issues and which at‐risk populations are not participating in online conversations and are therefore missing out on opportunities for health education. For example, data analyses might show gender gaps in which health issues receive online attention (Vraga et al, 2018) or identify when media engagement about a health issue is being displaced by political campaigns (Vraga et al, 2017). Understanding what information about a public health issue is missing on social media enables organizations to update their communication strategies.…”
Section: Opportunity: Evaluating Communication Impactmentioning
confidence: 99%
“…Prominent examples of such initiatives include Data.gov in the U.S. and OpenKenya [113] in the Republic of Kenya (see [114] for how such data can be used). The ever-increasing popularity of social media, enabled by Web 2.0 technology, is expanding the sources and volume of social data relevant to our daily lives through applications such as Facebook, Twitter, and Instagram, and these open sources are allowing researchers to explore a vast range of topics, including opinions during elections [115], opinions on public health [116], data on disease outbreaks [117], and studies of the connections between people and places [118,119]. The relevance and management of open-source data has become more important than ever, and they are well-positioned to support the quantitative study of disasters through the use of new computational methods, such as machine learning, natural language processing, sentiment analysis, and artificial intelligence [120].…”
Section: Information Retrieval and Open Data Systemsmentioning
confidence: 99%